ANALISIS PENERAPAN PEMBELAJARAN BERDIFERENSIASI DENGAN MODEL DISCOVERY LEARNING PADA PEMBELAJARAN MATEMATIKA KELAS VIII DI SMP NEGERI 1 AMPEK ANGKEKTAHUN PELAJARAN 2023/2024 - Tharwati Fadhilah; Iltavia Iltavia; Rosnidar (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
This research is a qualitative descriptive research with a case study approach in the application of differentiated learning. The aim of this research is to describe differentiated mathematics learning using the discovery learning model to increase student activity in the classroom in the learning process. This research was carried out in line with practical field experience carried out by researchers at SMP Negeri 1 Ampek Angkek. This research also aims to improve the current learning system where teachers still use conventional methods in learning. So that students' activeness in learning in class is not visible and students' understanding of mathematical concepts is low. The subjects of this research were students in class VIII-1. The choice of class VIII-1 was due to the characteristics of students with different abilities, in accordance with the objectives of implementing differentiated learning.